Knowledge sourcing from advanced markets subsidiaries: political embeddedness and reverse knowledge transfer barriers in emerging-market multinationals. (13th March 2017) - Ciabuschi, Francesco; Kong, Lingshuang; Su, Cong
Abstract: This article focuses on emerging-market multinationals and their intent to source knowledge from advanced countries. A single in-depth case study of a Chinese state-owned multinational is used to shed light on the relationship between political embeddedness and the potential to reverse knowledge transfer from advanced market subsidiaries. Specifically, we argue that a strong home-country political embeddedness enhances specific organizational barriers to reverse knowledge transfer, which undermines the strategic intent of knowledge-seeking internationalization, common to much Foreign Direct Investment (FDI) by emerging-market multinationals in recent years. This article contributes to research on knowledge sourcing within the context of south-north FDI by highlighting specific effects of political embeddedness at organizational level, which are critical for the possibilities to reverse knowledge transfer; our study is also relevant to international business, as new empirical insights related to the international organization and management of state-owned multinationals are discussed.